2022
DOI: 10.1172/jci146926
|View full text |Cite
|
Sign up to set email alerts
|

Smad7 effects on TGF-β and ErbB2 restrain myofibroblast activation and protect from postinfarction heart failure

Abstract: Repair of the infarcted heart requires TGF-β/Smad3 signaling in cardiac myofibroblasts. However, TGF-β–driven myofibroblast activation needs to be tightly regulated in order to prevent excessive fibrosis and adverse remodeling that may precipitate heart failure. We hypothesized that induction of the inhibitory Smad, Smad7, may restrain infarct myofibroblast activation, and we examined the molecular mechanisms of Smad7 actions. In a mouse model of nonreperfused infarction, Smad3 activation triggered Smad7 synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 78 publications
1
30
0
Order By: Relevance
“…The inhibitory Smad, Smad7, serves as a potent endogenous negative regulator of TGF‐β actions, restraining TGF‐β signaling cascades in many different cell types 31,75–77 . In macrophages, the role of Smad7 as a negative regulator of TGF‐β‐mediated actions remains controversial, as various studies have produced conflicting results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The inhibitory Smad, Smad7, serves as a potent endogenous negative regulator of TGF‐β actions, restraining TGF‐β signaling cascades in many different cell types 31,75–77 . In macrophages, the role of Smad7 as a negative regulator of TGF‐β‐mediated actions remains controversial, as various studies have produced conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory Smad, Smad7, serves as a potent endogenous negative regulator of TGF-β actions, restraining TGF-β signaling cascades in many different cell types. 31,[75][76][77] In macrophages, the role of Smad7 as a negative regulator of TGF-βmediated actions remains controversial, as various studies have produced conflicting results. Experiments in a viral infection model suggested that induction of Smad7 in macrophages may trigger inflammation, abrogating the anti-inflammatory effects of TGF-β.…”
Section: Tgf-β Signaling Cascades Regulate Macrophage Phenotype In Th...mentioning
confidence: 99%
See 1 more Smart Citation
“…Our group was the first to demonstrate that two different miRs, namely miR-92a ( 26 ) and miR-195 ( 35 ), act as transcriptional regulators of SMAD7, an inhibitor of α-SMA, which is a well-established marker of myofibroblast activation ( 58 ). We found that miR-92a is significantly upregulated in cardiomyocyte-derived exosomes and in fibroblasts isolated after MI compared with SHAM conditions, indicating that miR-92a is transferred to fibroblasts in form of exosomal cargo and is essential for the activation of cardiac myofibroblast ( 26 ).…”
Section: Effects Of Micrornas On Cardiac Fibroblasts Post-mimentioning
confidence: 99%
“…They revealed that Smad7 had an inhibitory effect on TGF-β expression in fibroblasts by promoting TβR and R-Smad turnover, leading to the downregulation of Smad2 and Smad3 molecules. This resulted in reduced myofibroblastic activity and decreased synthesis of EMPs [ 122 ]. Additionally, the TGF-β1/Smad signaling pathways are regulated by Slit2.…”
Section: Anti-fibrotic Therapiesmentioning
confidence: 99%